Reading in Proust's A la recherche 'le delire de la lecture' - Watt, Adam A. (Adam Andrew), 1979- (Oxford : Oxford University Press, 2009)
Through close textual analysis of the scenes of reading in Proust's 'A la recherche du temps perdu', Adam Watt offers an invigorating study of the novel and previously unacknowledged paths through it.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Proust, Marcel, -- 1871-1922.; Proust, Marcel, -- 1871-1922 -- Criticism and interpretation; Books and reading in literature